2016
DOI: 10.1002/jhm.2600
|View full text |Cite
|
Sign up to set email alerts
|

How well do patients and providers agree on the severity of dyspnea?

Abstract: BACKGROUND Understanding the severity of patients' dyspnea is critical to avoid under‐ or overtreatment of patients with acute cardiopulmonary conditions. OBJECTIVE To evaluate the agreement between dyspnea assessment by patients and healthcare providers and to explore which factors contribute to discordance in assessment. DESIGN, SETTINGS AND PARTICIPANTS Prospective study of patients hospitalized for acute cardiopulmonary diseases at an urban teaching hospital. INTERVENTION AND MEASUREMENTS A numerical ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…The study found the patients themselves reported higher dyspnoea scores than the nurses and physicians perceived they experienced. Likewise, a study from the United States of America also had patients and health care professionals assess the patients' perceived dyspnoea, and found poor agreement between the two [15]. These studies emphasise the need for the patient's own assessment, dyspnoea is a devastating symptom and the ability to detect relief is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found the patients themselves reported higher dyspnoea scores than the nurses and physicians perceived they experienced. Likewise, a study from the United States of America also had patients and health care professionals assess the patients' perceived dyspnoea, and found poor agreement between the two [15]. These studies emphasise the need for the patient's own assessment, dyspnoea is a devastating symptom and the ability to detect relief is essential.…”
Section: Discussionmentioning
confidence: 99%
“…oxygen saturation, and the degree of dyspnoea [11][12][13]. Furthermore, previous studies have suggested there is poor correlation between health care professionals' and patient's assessment of dyspnoea intensity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For a variety of pathologies, from psoriasis and rheumatoid arthritis to urinary symptoms, endometriosis, and depression, numerous studies have identified significant discordance in patient and physician perceptions of disease severity ( 21 27 ). In surgical patients, the literature is more limited.…”
Section: Introductionmentioning
confidence: 99%
“…Personal caregivers’ ratings of dyspnea agreed well with the patients’ own ratings, but this was far from being the case for the nurses’ ratings. The poor aptitude of nurses, physiotherapists, and physicians in identifying dyspnea in their patients has been described before (1113), but this is the first time that a comparison has been conducted with the corresponding aptitude of personal caregivers, who, notably, never failed to detect dyspnea.…”
mentioning
confidence: 77%